Study to Evaluate the Efficacy and Safety of Topical Lipid-based Amphotericin B Gel 0.1% in Patients with Cutaneous Mycosis Resistant to Conventional Therapy - Mamatha Kamarthi; Raghav M V; Laxminarayana Kamath; Revathi T N (Pharmacology and Clinical Pharmacy Research, 2022)
The last few years have seen a significant rise in the incidence of cutaneous mycosis infections resistant to conventional therapy. Topical nanostructured lipid formulations of Amphotericin B have emerged as a novel system to tackle this menace. The present study is an open-label, single-arm, prospective study to analyze the efficacy and safety of topical nanostructured lipid-based Amphotericin B gel in treating patients attending Dermatology OPD, Victoria hospital, with cutaneous mycosis resistant to conventional therapy. Thirty patients diagnosed with tinea corporis/cruris resistant to conventional therapy were included in the study.  Patients were advised to apply amphotericin B gel 0.1% on the affected area twice daily for four weeks. Outcome parameters like pruritus, erythema, vesicles, desquamation, and KOH mount were noted weekly for the assessment of efficacy and safety.  One-way ANOVA was used for statistical analysis. After treatment with Amphotericin B gel, patients showed a statistically significant reduction in pruritus, erythema, vesicles, and desquamation from baseline across time towards the end of 4 weeks (p<0.05).  Also, the Mean total score of all symptoms, which was 8.3±3.1 at baseline, was reduced to 0.9±0.7 at the end of the 4th week (p<0.05). All the patients treated were mycologically negative for KOH mount at the end of the study period. No serious adverse drug reactions were reported to treatment. To conclude, topical nanostructured lipid-based amphotericin B gel in patients with cutaneous mycosis resistant to conventional treatment was efficacious and safe.